2014
DOI: 10.1098/rsif.2014.0834
|View full text |Cite
|
Sign up to set email alerts
|

Universal predictability of mobility patterns in cities

Abstract: Despite the long history of modelling human mobility, we continue to lack a highly accurate approach with low data requirements for predicting mobility patterns in cities. Here, we present a population-weighted opportunities model without any adjustable parameters to capture the underlying driving force accounting for human mobility patterns at the city scale. We use various mobility data collected from a number of cities with different characteristics to demonstrate the predictive power of our model. We find … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 42 publications
(76 reference statements)
5
161
0
Order By: Relevance
“…To evaluate the performance of the models we investigated the travel distance distribution by three models based on ground truth data. Travel distance distribution is an important statistical property to capture human mobility behaviours (Yan et al, 2014). As shown in Figure (2) it can be found that the distribution of travel distance estimated by the rank-based model has a good accordance with the ground truth data compared to the other models.…”
Section: Evaluation Of Modelsmentioning
confidence: 48%
See 3 more Smart Citations
“…To evaluate the performance of the models we investigated the travel distance distribution by three models based on ground truth data. Travel distance distribution is an important statistical property to capture human mobility behaviours (Yan et al, 2014). As shown in Figure (2) it can be found that the distribution of travel distance estimated by the rank-based model has a good accordance with the ground truth data compared to the other models.…”
Section: Evaluation Of Modelsmentioning
confidence: 48%
“…Since the 1940s, various models such as gravity model (Zipf, 1946), intervening opportunity model (Stouffer, 1940), radiation model (Simini et al, 2012), rank-based model (Noulas et al, 2012) and population-weighted opportunities (PWO) model (Yan et al, 2014) have been proposed for estimation of OD matrix. In this study, the three following models have been utilized to compare their performance for LBSN data analysis:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One final fit statistic, a modified Sorensen similarity index (SSI), is included within the SpInt module because it has become increasingly popular in some spatial interaction literature that deals with non-parametric models (Lenormand et al 2012, Masucci et al 2012, Yan et al 2013. Using the same symbol definition from the SRMSE, the SSI is defined as,…”
Section: Model Fit Statisticsmentioning
confidence: 99%